2021
DOI: 10.1093/abbs/gmab103
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibitor LF3 restrains the development of pulmonary hypertension through the Wnt/β-catenin pathway

Abstract: Pulmonary hypertension (PH) associated with congenital heart disease is a progressive hemodynamic disease that can lead to increased pulmonary vascular resistance, vascular remodeling, and even right heart failure and death. LF3 is a novel inhibitor of the reporter gene activity of β-catenin/TCF4 interaction in the Wnt/β-catenin signal pathway. However, whether this action of LF3 can prevent PH development remains unclear. In this study, we investigated the therapeutic effect of LF3 in rat primary pulmonary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“… 47 , 48 , 49 Moreover, LF3 (an inhibitor of the interaction between TCF4 and β‐catenin) inhibited the progression of PH. 50 This evidence demonstrated the correlation between TCF4/β‐catenin and PH. Moreover, our results showed that overexpression of TCF4 significantly promoted the proliferation, migration, and phenotype switch of hypoxia‐induced PASMCs, and significantly reversed circ_0016070 silencing‐mediated effects.…”
Section: Discussionmentioning
confidence: 72%
“… 47 , 48 , 49 Moreover, LF3 (an inhibitor of the interaction between TCF4 and β‐catenin) inhibited the progression of PH. 50 This evidence demonstrated the correlation between TCF4/β‐catenin and PH. Moreover, our results showed that overexpression of TCF4 significantly promoted the proliferation, migration, and phenotype switch of hypoxia‐induced PASMCs, and significantly reversed circ_0016070 silencing‐mediated effects.…”
Section: Discussionmentioning
confidence: 72%
“…Activation of Wnt/β-catenin signaling also induces PASMC proliferation and vascular remodeling by inducing the expression of the downstream positive effectors Cyclin D1 and c-Myc. LF3, a small molecule, blocks the interaction between β-catenin and TCF4 and inhibits the downstream gene expression, thus preventing the proliferation and migration of PASMCs in rats with PH (Lei et al, 2021). We also recently revealed that resolvin E1 (RvE1), a pro-resolving lipid mediator, suppresses hypoxia-induced PASMC proliferation and experimental PH by inhibiting proliferative Wnt7a/β-catenin signaling (Liu et al, 2021).…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%
“…CWP232291, a first‐in‐class peptidomimetic drug, decreases β‐catenin by activating caspases and shows anticancer activity against relapsed or refractory myeloma 353 . Moreover, several compounds, such as LF3 and KYA1797K/KY1220, also effectively decrease the activation of Wnt pathway by targeting the β‐catenin/TCF complex 354–356 . In preclinical studies, both LF3 and KYA1797K/KY1220 effectively suppress the growth of colon cancer by disrupting the critical interaction between β‐catenin and TCF4 357,358 …”
Section: Targeting Oncofetal Reprogramming In Cancer Therapymentioning
confidence: 99%
“…353 Moreover, several compounds, such as LF3 and KYA1797K/KY1220, also effectively decrease the activation of Wnt pathway by targeting the β-catenin/TCF complex. [354][355][356] In preclinical studies, both LF3 and KYA1797K/KY1220 effectively suppress the growth of colon cancer by disrupting the critical interaction between β-catenin and TCF4. 357,358 The development of Notch signaling inhibitors necessitates a thorough understanding of its diverse and complex role in various cancers [367][368][369] (Figure 3).…”
Section: Targeting Developmental Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation